Edmond Goblot's (1858–1935) Selected Effects Theory of Function: A Reappraisal. Issue 5 (December 2021) - Garson, Justin
Abstract : At the beginning of the twentieth century, the French philosopher of science Edmond Goblot wrote three prescient papers on function and teleology. He advanced the remarkable thesis that functions are, as a matter of conceptual analysis, selected effects. He also argued that "selection" must be understood broadly to include both evolutionary natural selection and intelligent design. Here, I do three things. First, I give an overview of Goblot's thought. Second, I identify his core thesis about function. Third, I argue that, despite its ingenuity, Goblot's expansive construal of function cannot be right. Still, Goblot deserves long-overdue credit for his work.